2005
DOI: 10.1111/j.1440-1797.2005.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic serum protein concentrations differ between nightly nocturnal and conventional haemodialysis

Abstract: We concluded that NHD is a modality that facilitates the use of a low UFR and hence the slow removal of volume which, in turn, results in a minimal perturbation of the normal recumbent volume distribution mechanism and the partial preservation of the normal physiological response to recumbency of the serum protein concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The study by Wiggins et al reported a simple but significant difference in the behavior of a range of serum proteins, including the S.Alb, between patients on routine CHD and those undertaking NHHD 6 10 . They found that, as expected from intradialytic hemo‐concentration, the S.Alb increased from the predialysis baseline in CHD patients by 6.5% but, surprisingly, in NHHD 6 patients the S.Alb fell by 2.4% from the predialysis baseline (p<0.001) with a modality‐to‐modality difference of 8.9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Wiggins et al reported a simple but significant difference in the behavior of a range of serum proteins, including the S.Alb, between patients on routine CHD and those undertaking NHHD 6 10 . They found that, as expected from intradialytic hemo‐concentration, the S.Alb increased from the predialysis baseline in CHD patients by 6.5% but, surprisingly, in NHHD 6 patients the S.Alb fell by 2.4% from the predialysis baseline (p<0.001) with a modality‐to‐modality difference of 8.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The serum albumin (S.Alb) has long been regarded as a marker of dialysis outcome, a low S.Alb being associated with a poor nutritional status and a high risk of mortality 8 . More recently, however, Wiggins et al have suggested the S.Alb as a physiologic surrogate for intradialytic changes in volume status during nocturnal hemodialysis 9,10 . These authors reported significant pattern differences between the predialysis and postdialysis S.Alb in 2 matched patient cohorts, one undergoing seated 4 hr/session CHD and the other, a recumbent 8 hr/session, 6 nights/week nocturnal home hemodialysis (NHHD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have shown decreased serum albumin levels with DNHD. 60,61 Further stud-ies are necessary to assess affect of NDHD on malnutrition and inflammation.…”
Section: Nutritionmentioning
confidence: 99%